Depositional time trends of phosphorous accumulation in a dated sediment core from the northwestern Arabian Gulf: Can phosphorous be used to support 210Pb chronologies in coastal aquatic sediments?. (May 2021) - Gevao, Bondi; Uddin, Saif; Fowler, Scott W.; Behbehani, Montaha; Aba, Abdulaziz
Abstract: The use of 210 Pb dating for the reconstruction of contaminant profiles in undisturbed sediments is the most widely acceptable technique historically. Due to the uncertainties associated with the technique, dating of sediments have often been supported by ancillary evidence such as an alternative historical marker in the catchment that is preserved in the sedimentary records. The most widely used verification marker is 137 Cs, which is attributed to global fallout from past nuclear weapons testing, and the Chernobyl accident. In the southern hemisphere, and the mid-latitudes, the 137 Cs signal from Chernobyl fallout is often absent from the sedimentary records making it very difficult to verify the 210 Pb chronologies in these natural archives. This study reports the spatial and temporal variability of total phosphorus (TP) and its forms in sediments from Kuwait Bay and provides evidence of the possibility of using Phosphorous as a potential marker to support dates derived from 210 Pb dating. In the current study we report the spatial and temporal variations in the concentrations of Phosphorus from near-shore sediments from Kuwait. The mean (and range) of TP concentration in surficial sediments is 19.4 (12.2 to 24) μmol-P g −1 dry weight. The highest concentrations were measured in the deepest portions of the Bay which is characterized by fine grained sediments. The vertical profile of TP in the sediments was characterized by a gradual increase in concentration from lower layers to a subsurface maximum (at approximately 4–5 cm) followed by an exponential decrease to the sediment-water interface. The sedimentary TP profile correlated remarkably well with changes in the population of Kuwait over the last three decades, suggesting that wastewater inputs into the Bay from treatment plants are an important source of phosphorus in the coastal waters. The decrease in concentration in sediment deposited over the last five years of the core is explained by the commissioning of an improved wastewater treatment plant with higher phosphorus removal efficiency. These fluctuations preserved in the sedimentary records linked to identifiable historical events provides powerful evidence that this nutrient associated with wastewater inputs in coastal aquatic environments can be used as ancillary information to support 210 Pb dating. Highlights: The absence of a Chernobyl 137 Cs horizon in a large part of the world makes it difficult to verify 210 Pb sediment dating. Alternate horizons that have a clear temporal imprint can be effective in verifying 210 Pb derived chronologies. Phosphorous has been used to support 210 Pb chronologies and can be extended to other coastal areas.